2015
DOI: 10.1681/asn.2014080799
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in Children with Steroid-Dependent Nephrotic Syndrome

Abstract: Steroid-dependent nephrotic syndrome (SDNS) carries a high risk of toxicity from steroids or steroid-sparing agents. This open-label, noninferiority, randomized controlled trial at four sites in Italy tested whether rituximab is noninferior to steroids in maintaining remission in juvenile SDNS. We enrolled children age 1-16 years who had developed SDNS in the previous 6-12 months and were maintained in remission with high prednisone doses ($0.7 mg/kg per day). We randomly assigned participants to continue pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
143
2
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 48 publications
5
143
2
12
Order By: Relevance
“…The steroids were tapered and withdrawn in the following month in both groups. Patients treated with rituximab (375 mg/m 2 ) completed steroid withdrawal as indicated earlier; 80% of these patients maintained drug-free remission at 1 year, whereas patients who did not receive rituximab had recurrence of proteinuria shortly after steroid elimination (27). The median relapse-free survival time after repeated rituximab infusions in the follow-up study of this trial cohort was 18 months (95% confidence interval, 9 to 32 months).…”
Section: Randomized Controlled Trialsmentioning
confidence: 79%
See 4 more Smart Citations
“…The steroids were tapered and withdrawn in the following month in both groups. Patients treated with rituximab (375 mg/m 2 ) completed steroid withdrawal as indicated earlier; 80% of these patients maintained drug-free remission at 1 year, whereas patients who did not receive rituximab had recurrence of proteinuria shortly after steroid elimination (27). The median relapse-free survival time after repeated rituximab infusions in the follow-up study of this trial cohort was 18 months (95% confidence interval, 9 to 32 months).…”
Section: Randomized Controlled Trialsmentioning
confidence: 79%
“…Between 2011 and 2015, five clinical trials on the use of rituximab in idiopathic nephrotic syndrome were reported: four as journal articles (27)(28)(29)(30) and one in abstract form. Results of four prospective studies were also published in the same period (see below) (27,31,32).…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
See 3 more Smart Citations